Engineering complex phenotypes in industrial strains - Patnaik, Ranjan, 1969- (Wiley, 2013)
"This book details the current and future tools used in the production of bulk chemicals and biofuels developed from renewable biomass using green technologies. It describes in depth the technology used to unravel the complexity of microbial metabolism in order to produce engineering strains at time scales much faster than would occur naturally. It also highlights the advantages and drawbacks of all methods and tools used in multiple disciplines for genome engineering of complex phenotypes. Case-study examples on applying the tools reinforce the fundamental concepts. A must for research and development biochemists and engineers"--